Double-sided roughened composite current collector copper foil and preparation method thereof

By using double-sided roughened composite fluid-collection copper foil in lithium-ion batteries and lithium metal batteries, the battery short circuit and fire explosion problems caused by disordered growth of lithium dendrites are solved, and the energy density and safety performance of the battery are improved.

CN119650710APending Publication Date: 2025-03-18JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411812044.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The double-sided photoelectrolytic copper foil used in existing lithium-ion batteries and lithium metal batteries cannot effectively guide the orderly growth of lithium dendrites, resulting in the puncture of the separator, increasing the risk of battery short circuit and fire explosion. At the same time, the high density of current collectors limits the battery's energy density and cycle life.

Method used

Double-sided roughened composite fluid-collection copper foil, which includes a polymer core layer and a multi-layer structure copper layer, is used to form roughened copper foil through oxygen plasma cleaning, magnetron sputtering, pulse electrochemical deposition and other processes to reduce the density and interface differences of the copper foil.

Benefits of technology

It improves the mass energy density of the battery, enhances the interface impedance uniformity between the current collector and the electrode material, reduces the risk of lithium dendrites piercing the diaphragm, and improves the safety performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180776820000081
    Figure BDA0005180776820000081
  • Figure HDA0005180776840000011
    Figure HDA0005180776840000011
  • Figure HDA0005180776840000012
    Figure HDA0005180776840000012
Patent Text Reader

Abstract

The invention relates to a double-sided roughened composite current collector copper foil and a preparation method thereof, the composite current collector copper foil comprises a polymer core layer, and the outer surface of the polymer core layer is sequentially provided with a sputtering copper layer, an electroplating copper layer, a roughened copper layer and an anti-oxidation layer. Compared with the traditional double-sided polished copper foil, the double-sided roughened composite current collector copper foil has the following characteristics: (1) the overall density of the composite copper foil is reduced due to the introduction of the light-weight and low-density polymer film, and the mass energy density of a battery is favorably improved; (2) the double-sided impedance uniformity is improved, the difference degree of the upper and lower surfaces of the copper foil can be reduced through double-sided roughening treatment, and the uniformity of the interface impedance between the current collector and the electrode material can be improved; and (3) the safety is improved, the roughened copper foil can guide the growth of lithium dendrites, and the risk that the diaphragm is punctured is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy material processing, and in particular relates to a double-sided roughened composite current collector copper foil and a preparation method thereof. Background Art

[0002] Power batteries are one of the core components of new energy vehicles, which directly determine the driving range, service life and safety performance of new energy vehicles. Lithium-ion batteries and lithium metal batteries have the advantages of high energy density, good safety performance and environmental friendliness, and have become the mainstream electrochemical energy storage devices for power batteries of new energy vehicles. With the gradual popularization of new energy vehicles, customers have put forward new and higher requirements for the driving range, safety performance and service life of power batteries.

[0003] From the perspective of materials, lithium-ion batteries and lithium metal batteries are mainly composed of positive electrode materials, negative electrode materials, electrolytes, separators and current collectors. Among them, copper foil is generally used as the negative electrode current collector, and aluminum foil is generally used as the positive electrode current collector. The current collector plays the following roles in lithium-ion batteries and lithium metal batteries: (1) input and output current to realize the battery charging and discharging process; (2) carry the negative electrode material to ensure that the battery has a certain structural strength. It should be pointed out that: on the one hand, the current collector does not contribute to the energy density of lithium-ion batteries and lithium metal batteries, and on the other hand, copper foil is the material with the highest mass density among all the components of lithium-ion batteries and lithium metal batteries. Therefore, in order to improve the energy density of lithium-ion batteries and lithium metal batteries, the mass fraction of the current collector can be reduced while ensuring that the current conduction is not affected. Existing studies have found that when the thickness of copper foil exceeds 1.0μm, the current carrying capacity of the current collector can meet the requirements of high-rate charging and discharging of lithium-ion batteries and lithium metal batteries. Limited by the current production equipment and the mechanical properties of copper foil, lithium-ion batteries currently produced on the market mainly use copper foil with a thickness of 6μm or more as the negative electrode current collector. Using low-density materials to form composite copper foil with copper can effectively reduce the density of the current collector, which is beneficial to improving the energy density of lithium-ion batteries and lithium metal batteries and increasing the cruising range of new energy vehicles.

[0004] During the charging and discharging process of lithium-ion batteries and lithium metal batteries, the disordered growth of lithium dendrites will pierce the diaphragm, causing the battery to short-circuit and cause the battery to catch fire and explode. The disordered growth of lithium dendrites poses a serious threat to the safety of the battery. It should be pointed out that the double-sided photoelectrolytic copper foil currently used cannot effectively guide the orderly growth of lithium dendrites. By designing the structure of the current collector to form a structure with a certain contour, the growth of lithium dendrites can be guided, reducing the risk of lithium dendrites piercing the diaphragm and causing a battery short circuit, which can improve the safety performance of lithium-ion batteries and lithium metal batteries to a certain extent.

[0005] The interface between the current collector and the electrode material has a significant impact on the cycle life of lithium-ion batteries and lithium metal batteries. Traditional double-sided photoelectrolytic copper foil is grown by electrochemical deposition on the surface of a titanium cathode roller. One side of the copper foil is mirror-symmetrical with the crystal structure of the titanium roller, while the other side is mainly affected by additives and electric fields. Therefore, there are certain differences in the crystal structure and roughness of the upper and lower surfaces of the traditional double-sided photoelectrolytic copper foil. The two interfaces formed by the upper and lower surfaces of the copper foil and the electrode material also show certain differences accordingly. During the long-term charging and discharging process, the Joule heat generated at the copper foil-electrode material interface is different due to the difference in interface resistance, which may cause interface deformation, thereby affecting the battery cycle life. Through material engineering and structural design, the differences in crystal structure and roughness between the upper and lower surfaces of the copper foil can be reduced, thereby reducing the interface difference between the copper foil surface and the electrode material. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a double-sided roughened composite current collector copper foil and a preparation method thereof. The composite current collector copper foil has the following advantages: (1) Lightweight. The introduction of a low-density polymer film reduces the overall density of the composite copper foil, which is beneficial to improving the mass energy density of the battery; (2) Double-sided impedance uniformity is improved. The double-sided roughening treatment can reduce the difference between the upper and lower surfaces of the copper foil, which is beneficial to improving the uniformity of the interface impedance between the current collector and the electrode material; (3) Safety is improved. The roughened copper foil can guide the growth of lithium dendrites and reduce the risk of puncture of the diaphragm.

[0007] The present invention provides a double-sided roughened composite current collector copper foil, the composite current collector copper foil comprises a polymer core layer, and the outer surface of the polymer core layer is also provided with a sputtered copper layer, an electroplated copper layer, a roughened copper layer and an anti-oxidation layer in sequence. Figure 1 As shown, both sides of the polymer core layer have a sputtered copper layer, an electroplated copper layer, a roughened copper layer and an anti-oxidation layer.

[0008] Preferably, the polymer core layer is made of one or more of polyethylene, polypropylene, polyimide, polyphenylene sulfide and polyethylene terephthalate.

[0009] Preferably, the thickness of the polymer core layer is between 6-18 μm, the surface roughness Rz of the polymer core layer is between 0.1-0.5 μm, the line roughness Sz is between 0.1-0.6 μm, and the interface expansion area ratio Sdr is between 0.05-0.25%.

[0010] Preferably, the surface wettability dyne value of the composite current collector copper foil is not less than 50 dyn / cm.

[0011] The present invention also provides a method for preparing a double-sided roughened composite current collector copper foil, comprising the following steps:

[0012] (1) cleaning the surface of the polymer film by oxygen plasma, removing surface impurities and performing activation pretreatment on the surface to obtain a polymer core layer;

[0013] (2) depositing a transition metal layer and a seed copper layer on the surface of the polymer core layer in sequence by magnetron sputtering;

[0014] (3) electro-depositing a copper layer with a thickness of micrometers on the surface of the seed copper layer by pulse electrochemical deposition assisted by additives, i.e., an electroplated copper layer;

[0015] (4) roughening the surface of the copper-plated layer by pulse electrochemical deposition assisted by an additive to obtain a roughened copper layer;

[0016] (5) forming an anti-oxidation layer on the surface of the roughened copper layer by physical and chemical means to obtain a double-sided roughened composite current collector copper foil.

[0017] Preferably, the process parameters of the activation pretreatment in step (1) are: plasma power between 1000-2000 W, and treatment time between 5-15 min.

[0018] Preferably, the thickness of the transition metal layer in step (2) is between 10-50 nm, and the composition of the transition metal layer is one or more of titanium, chromium, zinc, copper, and titanium-copper alloy.

[0019] Preferably, the thickness of the seed copper layer in step (2) is between 20-100 nm.

[0020] Preferably, the thickness of the electroplated copper layer in step (3) is between 1.0-1.5 μm.

[0021] Preferably, the additive used in the process of forming the electroplated copper layer in step (3) is one or more of urea-choline chloride, sodium ethylenediaminetetraacetate, polyethylene glycol, dodecyltrimethylammonium bromide, and sodium dodecylbenzenesulfonate, and the concentration of the additive is between 5-25 mg / L.

[0022] Preferably, the average current density of the pulse current during the formation of the electroplated copper layer in step (3) is 1500-4500 A / m 2 The duty cycle is between 0-50% and the frequency is between 0-2000Hz.

[0023] Preferably, the additive used in the roughening process in step (4) is one or more of sodium tungstate, ammonium molybdate, benzotriazole, carboxybenzotriazole, and mercaptobenzothiazole, and the concentration of the additive is between 10-30 mg / L.

[0024] Preferably, the average current density of the pulse current during the roughening process in step (4) is between 800 and 1600 A / m 2 The duty cycle is between 20-67% and the frequency is between 1000-3000Hz.

[0025] Preferably, after the roughening treatment in step (4), the copper foil surface line roughness Rz is between 2.0-3.0 μm, the surface roughness Sz is between 2.5-3.5 μm, and the interface expansion area ratio Sdr is between 20-50%.

[0026] Preferably, the physicochemical method in step (5) includes one or more of electrochemical deposition, physical coating, and vapor deposition.

[0027] Preferably, the main component of the anti-oxidation layer in step (5) is one or more of zinc, chromium, and a silane coupling agent; the formation of the anti-oxidation layer can prevent the copper foil from oxidative discoloration at a temperature not exceeding 150° C. and a time not exceeding 30 min, thereby preventing the copper foil from oxidative discoloration during storage, processing, and use.

[0028] Beneficial Effects

[0029] Compared with the traditional double-sided plain copper foil, the double-sided roughened composite current collector copper foil of the present invention has the following characteristics: (1) Lightweight. The introduction of low-density polymer film reduces the overall density of the composite copper foil, which is beneficial to improving the mass energy density of the battery; (2) Double-sided impedance uniformity is improved. The double-sided roughening treatment can reduce the difference between the upper and lower surfaces of the copper foil, which is beneficial to improving the uniformity of the interface impedance between the current collector and the electrode material; (3) Safety is improved. The roughened copper foil can guide the growth of lithium dendrites and reduce the risk of puncturing the diaphragm. Therefore, the double-sided roughened composite current collector copper foil of the present invention has considerable application value in high-performance lithium-ion batteries and lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the structure of the double-sided roughened composite current collector copper foil of the present invention; wherein, L01 is a polymer core layer, L02 is a sputtered copper layer, L03 is an electroplated copper layer, L04 is a roughened copper layer, and L05 is an anti-oxidation layer.

[0031] Figure 2 Double-sided SEM images of the current collector copper foil prepared in Example 1 and Comparative Example 2; wherein, (a) Surface 1 of Example 1; (b) Surface 2 of Example 1; (d) Surface 1 of Comparative Example 2; (d) Surface 2 of Comparative Example 2.

[0032] Figure 3Double-sided laser confocal cloud images of the current collector copper foil prepared in Example 1 and Comparative Example 2; wherein, (a) Surface 1 of Example 1; (b) Surface 2 of Example 1; (d) Surface 1 of Comparative Example 2; (d) Surface 2 of Comparative Example 2. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] Example 1

[0035] The present invention provides a method for producing a double-sided roughened composite current collector copper foil, the specific contents of which are as follows:

[0036] S01. Polymer film pretreatment

[0037] A polypropylene film with a thickness of 6 μm was selected, and its surface was pretreated with oxygen plasma to obtain a polymer core layer L01. The parameters during the pretreatment process are as follows:

[0038] PP film line roughness Rz: 0.10μm;

[0039] PP film surface roughness Sz: 0.15μm;

[0040] PP film interface expansion area ratio Sdr: 0.05%;

[0041] Plasma power: 1000W;

[0042] Pretreatment time: 15min.

[0043] S02 sputtered copper layer

[0044] After a transition metal layer is deposited on the surface of the polymer core layer L01, a sputtered copper layer L02 is obtained by further sputtering. The parameters in the preparation process of the sputtered copper layer L02 are as follows:

[0045] Transition metal component: titanium (Ti);

[0046] Transition metal thickness: 10nm;

[0047] Sputtering copper layer power: 2500W;

[0048] Sputtering vacuum degree: 2.0*10 -4 Pa.

[0049] S03 electroplated copper layer

[0050] The polymer core layer L01 after sputtering is unrolled and run to the electrochemical deposition device for electroplating thickening treatment. The parameters of the electroplating thickening process are as follows:

[0051] Copper concentration: 100g / L;

[0052] H 2 SO 4 Concentration: 150g / L;

[0053] Urea concentration: 10mg / L;

[0054] Choline chloride concentration: 5 mg / L;

[0055] Average current density: 4500A / m 2 ;

[0056] Duty cycle: 50%;

[0057] Pulse frequency: 2000Hz.

[0058] S04 Roughening treatment

[0059] The electroplated thickened polymer-copper foil composite film is continued to run to the roughening treatment device for double-sided roughening treatment. The parameters in the double-sided roughening treatment process are as follows:

[0060] Copper concentration: 20g / L;

[0061] H 2 SO 4 Concentration: 100g / L;

[0062] Sodium tungstate concentration: 30mg / L;

[0063] Average current density: 800A / m 2 ;

[0064] Duty cycle: 20%;

[0065] Pulse frequency: 1000Hz.

[0066] S05 Anti-oxidation Treatment

[0067] The double-sided roughened composite copper foil is run into the anti-oxidation treatment device for anti-oxidation treatment. The parameters during the anti-oxidation treatment are as follows:

[0068] Zinc ion concentration: 2.5g / L;

[0069] Potassium pyrophosphate concentration: 50g / L;

[0070] pH: 11.0;

[0071] Electrolyte temperature: 35°C;

[0072] Current density: 50A / m 2 ;

[0073] Electrodeposition time: 10 s.

[0074] Example 2

[0075] The differences between this embodiment and embodiment 1 are that (1) the composition and thickness of the polymer film are adjusted, and the PP film with a thickness of 6 μm is replaced by a PET film with a thickness of 18 μm; (2) the transition metal is replaced by a titanium copper alloy with a thickness of 50 nm instead of a titanium with a thickness of 10 nm; (3) the additive in the electrochemical copper plating process is replaced by urea-choline chloride with EDTA-2Na with a concentration of 5 mg / L; and (4) the additive in the roughening treatment process is replaced by benzotriazole.

[0076] Example 3

[0077] The differences between this embodiment and embodiment 1 are that (1) the composition and thickness of the polymer film are adjusted, and the PP film with a thickness of 6 μm is replaced by a PE film with a thickness of 12 μm; (2) the transition metal is replaced by titanium with a thickness of 10 nm and zinc with a thickness of 20 nm; (3) the additive in the electrochemical copper plating process is replaced by urea-choline chloride and PEG with a concentration of 25 mg / L; (4) the additive in the roughening treatment process is replaced by carboxybenzotriazole.

[0078] Example 4

[0079] The differences between this embodiment and embodiment 1 are that (1) the composition and thickness of the polymer film are adjusted, and the PP film with a thickness of 6 μm is replaced by a PI film with a thickness of 18 μm; (2) the transition metal is replaced by titanium with a thickness of 10 nm and chromium with a thickness of 20 nm; (3) the additive in the electrochemical copper plating process is replaced by urea-choline chloride and SDS with a concentration of 15 mg / L; (4) the additive in the roughening process is replaced by mercaptobenzothiazole.

[0080] Example 5

[0081] The differences between this embodiment and embodiment 1 are that (1) the composition and thickness of the polymer film are adjusted, and the PP film with a thickness of 6 μm is replaced by a PPS film with a thickness of 12 μm; (2) the transition metal is replaced by titanium with a thickness of 10 nm and copper with a thickness of 20 nm; (3) the additive in the electrochemical copper plating process is replaced by urea-choline chloride and CTAB with a concentration of 10 mg / L; (4) the additive in the roughening treatment process is replaced by ammonium molybdate.

[0082] Example 6

[0083] The difference between this embodiment and embodiment 1 is that (1) the thickness of the sputtered copper layer is adjusted from 20 nm to 100 nm; (2) the average current density during the electrochemical copper plating process is increased from 4500 A / m 2 Adjusted to 1500A / m 2 , adjust the duty cycle from 50% to 20%, and adjust the pulse frequency from 2000 Hz to 1000 Hz; (4) adjust the average current density during the roughening process from 800 A / m 2 Adjusted to 1600A / m 2 , adjust the duty cycle from 20% to 67% and the pulse frequency from 1000Hz to 3000Hz.

[0084] Example 7

[0085] The differences between this embodiment and embodiment 1 are that (1) the thickness of the sputtered copper layer is adjusted from 20 nm to 50 nm; (2) the average current density during the electrochemical copper plating process is increased from 4500 A / m 2 Adjusted to 2500A / m 2 , adjust the duty cycle from 50% to 33%, and adjust the pulse frequency from 2000 Hz to 1500 Hz; (4) adjust the average current density during the roughening process from 800 A / m 2 Adjusted to 1200A / m 2 , adjust the duty cycle from 20% to 50% and the pulse frequency from 1000Hz to 2000Hz.

[0086] Example 8

[0087] The differences between this embodiment and embodiment 1 are as follows: (1) the thickness of the sputtered copper layer is adjusted from 20 nm to 75 nm; (2) the duty cycle in the electrochemical copper plating process is adjusted from 50% to 0%, and the pulse frequency is adjusted from 2000 Hz to 0 Hz; (4) the average current density in the roughening process is increased from 800 A / m 2 Adjusted to 1000A / m 2 , adjust the duty cycle from 20% to 40% and the pulse frequency from 1000Hz to 1500Hz.

[0088] Example 9

[0089] The difference between this embodiment and embodiment 1 is that (1) the thickness of the copper layer in the electrochemical copper plating process is adjusted, and the thickness of the copper layer is increased from 1.0 μm to 1.5 μm; (2) the composition of the anti-oxidation layer is adjusted, and the electrochemical zinc plating layer is replaced by a physical coating silane coupling agent.

[0090] Example 10

[0091] The difference between this embodiment and embodiment 1 is that (1) the thickness of the copper layer during the electrochemical copper plating process is adjusted, and the thickness of the copper layer is increased from 1.0 μm to 1.5 μm; (2) the composition of the anti-oxidation layer is adjusted, and the electrochemical zinc plating layer is replaced by vapor-deposited chromium.

[0092] Comparative Example 1

[0093] The difference between this comparative example and Example 1 is that a double-sided photoelectrolytic copper foil with a thickness of 8 μm is produced directly on the surface of the titanium cathode roller by direct current electrochemical deposition. The parameters in the production process of the double-sided photoelectrolytic copper foil are as follows:

[0094] Copper concentration: 100g / L;

[0095] H 2 SO 4 Concentration: 150g / L;

[0096] Brightener concentration: 2.5mg / L;

[0097] Concentration of moving agent: 6mg / L;

[0098] Leveling agent concentration: 7.5mg / L;

[0099] Chloride ion concentration: 15mg / L;

[0100] Current density: 7500A / m 2 ;

[0101] Cr(VI) concentration: 2.0 g / L;

[0102] pH value of passivation solution: 2.5;

[0103] Passivation current: 10A / m 2 .

[0104] Comparative Example 2

[0105] The difference between this comparative example and Example 1 is that (1) a double-sided electrolytic copper foil with a thickness of 8 μm is produced by direct current electrochemical deposition; (2) the double-sided copper foil is subjected to roughening treatment and anti-oxidation treatment to produce a double-sided roughened electrolytic copper foil. The parameters in the double-sided roughening and anti-oxidation treatment process are as follows:

[0106] Copper concentration: 20g / L;

[0107] H 2 SO 4 Concentration: 100g / L;

[0108] Sodium tungstate concentration: 30mg / L;

[0109] Current density: 2000A / m 2 ;

[0110] Cr(VI) concentration: 2.0 g / L;

[0111] Passivation current: 10A / m 2 ;

[0112] Passivation solution pH value: 11.5;

[0113] Passivation current: 20A / m 2 .

[0114] In order to more intuitively reflect the implementation effect of the present invention, the present invention uses a scanning electron microscope (SEM, TESCANVEGA3) and a laser confocal microscope (OLS-5100) to analyze and characterize the double-sided roughened copper foil produced by different process parameters of the embodiments and comparative examples. Figure 2 The SEM images of the microscopic morphology of the treated surface of the ultra-thin copper layer produced according to the parameters of Example 1 and Comparative Example 2 are shown. Figure 2 (a)(b) and Figure 2 (c)(d) It can be found that the double-sided roughened copper foil produced with different process parameters has significant differences in microscopic morphology. The roughened particle size of the double-sided roughened copper foil produced according to the process parameters of Example 1 is significantly larger than that of the copper foil sample produced according to the process parameters of Comparative Example 2. The difference in microscopic morphology may be due to the fact that the substrates of electrochemical deposition during the roughening process are not completely the same. The roughened substrate in Example 1 is a composite material composed of a polymer film and an extremely thin copper layer, and the roughened substrate in Comparative Example 2 is an 8μm copper layer. The resistivity of the two will be different to a certain extent.

[0115] Figure 3 The laser confocal cloud image of the double-sided roughened copper foil produced according to the parameters of Example 1 and Comparative Example 2 is shown. Different colors in the image represent different roughness. The red area indicates a relatively high roughness, and the blue area indicates a relatively low roughness. Figure 3 (a)(b) and Figure 3 (c) (d) It can be found that there are obvious differences in the surface profile distribution of the two samples. Figure 3 (c)(d) It can be observed Figure 3 The blue area in (a) and (b) is relatively darker, and the height difference of the roughened structure of the surface sample is relatively higher. Therefore, the roughening effect of the double-sided roughened copper foil produced according to the process parameters of Example 1 is relatively more obvious.

[0116] Table 1 further summarizes the physical properties of the double-sided roughened copper foil produced according to the process parameters of different embodiments and comparative examples. By analyzing and comparing the data in this table, it can be found that different polymer core layers, sputtering processes, electrochemical thickening and roughening processes have a significant impact on the physical properties of the double-sided roughened copper foil. Therefore, the selection of appropriate polymer films, sputtered metal layers and electrochemical deposition additives is of great significance to the performance of the composite current collector and the performance of lithium metal batteries and lithium ion batteries.

[0117] Table-1. Physical properties of double-sided roughened copper foil produced with different process parameters

[0118]

[0119] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A double-sided roughened composite current collector copper foil, characterized in that: The composite current collector copper foil comprises a polymer core layer, and the outer surface of the polymer core layer is also provided with a sputtered copper layer, an electroplated copper layer, a roughened copper layer and an anti-oxidation layer in sequence.

2. The double-sided roughened composite current collector copper foil according to claim 1, characterized in that: The polymer core layer is made of one or more of polyethylene, polypropylene, polyimide, polyphenylene sulfide and polyethylene terephthalate.

3. A method for preparing a double-sided roughened composite current collector copper foil, comprising the following steps: (1) cleaning the surface of the polymer film by oxygen plasma, removing surface impurities and performing activation pretreatment on the surface to obtain a polymer core layer; (2) depositing a transition metal layer and a seed copper layer on the surface of the polymer core layer in sequence by magnetron sputtering; (3) electro-depositing a copper layer with a thickness of micrometers on the surface of the seed copper layer by pulse electrochemical deposition assisted by additives, i.e., an electroplated copper layer; (4) roughening the surface of the copper-plated layer by pulse electrochemical deposition assisted by an additive to obtain a roughened copper layer; (5) forming an anti-oxidation layer on the surface of the roughened copper layer by physical and chemical means to obtain a double-sided roughened composite current collector copper foil.

4. The preparation method according to claim 3, characterized in that: The process parameters of the activation pretreatment in step (1) are: plasma power between 1000-2000W, and treatment time between 5-15min.

5. The preparation method according to claim 3, characterized in that: The thickness of the transition metal layer in step (2) is between 10-50 nm, and the composition of the transition metal layer is one or more of titanium, chromium, zinc, copper, and titanium-copper alloy; the thickness of the seed copper layer is between 20-100 nm.

6. The preparation method according to claim 3, characterized in that: The thickness of the electroplated copper layer in step (3) is between 1.0-1.5 μm; the additives used in the process of forming the electroplated copper layer are one or more of urea-choline chloride, sodium ethylenediaminetetraacetate, polyethylene glycol, dodecyltrimethylammonium bromide, and sodium dodecylbenzenesulfonate, and the concentration of the additives is between 5-25 mg / L.

7. The preparation method according to claim 3, characterized in that: The average current density of the pulse current in the process of forming the electroplated copper layer in step (3) is 1500-4500A / m 2 The duty cycle is between 0-50% and the frequency is between 0-2000Hz.

8. The preparation method according to claim 3, characterized in that: The additive used in the roughening process in step (4) is one or more of sodium tungstate, ammonium molybdate, benzotriazole, carboxybenzotriazole, and mercaptobenzothiazole, and the concentration of the additive is between 10-30 mg / L.

9. The preparation method according to claim 3, characterized in that: The average current density of the pulse current during the roughening process in step (4) is 800-1600 A / m 2 The duty cycle is between 20-67% and the frequency is between 1000-3000Hz.

10. The preparation method according to claim 3, characterized in that: The physicochemical method in step (5) includes one or more of electrochemical deposition, physical coating, and vapor deposition.

Citation Information

Patent Citations

  • Preparation method of ultra-thin copper foil with carrier

    CN115233262A

  • High-performance and conductive polysulfone copper foil composite material and preparation method thereof

    CN117430857A

  • Preparation method of light double-sided roughened special copper foil

    CN117845286A

  • Production method of double-sided roughened porous electrolytic copper foil

    CN118256961A

  • High-adhesion composite copper foil current collector and preparation method and application thereof

    CN118553919A